Analysis Of Community Attitudes In First Aid Of Traffic Accident - Afni, Anissa Cindy Nurul; Saputro, Sutiyo Dani (Universitas Aisyah Pringsewu, 2021)
Background: Death due to traffic accidents is a global issue. The World Health Organization (WHO) showed that deaths due to traffic accidents increase in developing countries such as Indonesia and Vietnam. It is not uncommon for the result of wrong actions when providing help. It increases injury and even causes death. Aim and objective: This research aimed to identify the factor that associates to attitudes community in providing first aid to a traffic accident. It adopted a descriptive correlative study of 31 members of youth organizations in Joglo Village, Surakarta District. Its sampling was selected by systematic random sampling. Result: The logistic regression analysis revealed two factors related to attitudes. It determined that the experience and knowledge of first aid correlated with attitudes community. The greatest strength of the relationship was the knowledge (OR=2.756) and the smallest was the experience (OR=-0,004). Conclusion: Personal experiences could be the basis for attitude formation if they leave a strong impression. People who have obtained information and experience will have a better chance of giving positive attitudes to provide help.Abstrak: Latar Belakang: Kematian akibat kecelakaan lalu linta merupakan isu global. World Health Organization (WHO) menunjukkan bahwa kematian akibat kecelakaan lalu lintas meningkat di negara berkembang seperti Indonesia dan vietnam. Kematian terjadi tidak jarang akibat dari tindakan yang salah saat memberikan pertolongan pertama. Hal ini dapat meningkatkan cedera dan kematian. Maksud dan tujuan: Penelitian ini bertujuan mengidentifikasi faktor-faktor yang berhubungan dengan sikap masyarakat dalam memebrikan pertolongan pertama pada kecelakaan lalu lintas. Penelitian ini merupakan studi deskriptif korelatif terhadap 31 anggota karang taruna Kelurahan Joglo, kabupaten Surakarta. Pengambilan sampel dilakukan secara sistematik random sampling. Hasil: Hasil analisis regresi logistik menunjukkan dua faktor yang berhubungan dengan sikap yaitu pengetahuan dan pengalaman dalam memberikan pertolongan pertama. Kekuatan hubungan terbesar adalah pengetahuan (OR=2,756) dan terkecil adalah pengalaman (OR = -0,004). Kesimpulan: Pengalaman pribadi akan menjadi dasar terbentuknya sikap karna ada kesan yang kuat. Seseorang yang memiliki pengetahuan dan pengalaman akan memiliki sikap positif dalam memberikan pertolongan pertama.